1039. Surveillance Blood Cultures Associated With Decreased Mortality in Gram-Negative Bacteremia. (26th November 2018) - Maskarinec, Stacey A; Van Duin, David; Ruffin, Felicia; Fowler Jr, Vance G; Thaden, Joshua T
Abstract: Background: Prior studies have suggested that surveillance blood cultures (SBCs) may not be indicated in the setting of Gram-negative bacteremia (GNB). However, it is unclear how particular microbial species influence the need for SBCs in GNB. Methods: We conducted a prospective cohort study of inpatients at Duke with Staphylococcus aureus bacteremia (SAB) and GNB from 2002–2015. Patients who died <24 hours from the first positive blood culture were excluded. Patients provided written informed consent. SBCs were defined as a blood culture drawn from 24 hours to 7 days from initial positive blood culture. Persistent bacteremia was defined as a positive SBC with the same organism. Statistical testing included Fishers exact and chi-square tests. Results: There were 2856 episodes of bacteremia over the study period (SAB: 1, 147 [40%]; GNB: 1, 709 [60%]). SBCs were drawn in 87% (1, 003/1, 147) of SAB patients and 64% (1, 097/1, 709) of GNB patients. SBC rates varied by GNB species ( P < 0.001), being more commonly drawn for those patients with Pseudomonas bacteremia (128/159 [80%]) than those with Escherichia bacteremia (377/592 [62%]). In GNB, acquisition of SBCs, regardless of positivity, was associated with decreased in-hospital mortality (177/1, 173 [15%] vs. 109/536 [20%]; P = 0.008). The in-hospital mortality benefit associated with SBCs varied with GNB species, including Pseudomonas (30/128 [23%] vs. 14/31 [45%]; P = 0.02) and Escherichia (33/377 [9%] vs. 37/215 [17%]; P = 0.003). In-hospital mortality in those with SAB was also lower when SBCs were drawn (143/1003 [14%] vs. 46/144 [32%]; P = 0.0001) (figure). In GNB, positive SBCs, relative to negative SBCs, was associated with increased in-hospital mortality (44/217 [20%] vs. 133/956 [14%]; P = 0.02). Persistent bacteremia occurred in 49% (494/1003) of SAB patients and 20% (217/1097) of GNB patients with SBCs. Persistent bacteremia risk differed by GNB species ( P = 0.004), and was highest among those with Stenotrophomonas maltophilia (9/19 [47%]) or Serratia (24/76 [31%]). Conclusion: Acquisition of SBCs in patients with GNB was associated with decreased mortality, and this was driven in part by species-specific differences. Disclosures: D. Van Duin, achaogen: Scientific Advisor, Consulting fee. shionogi: Scientific Advisor, Consulting fee. Allergan: Scientific Advisor, Consulting fee. Astellas: Scientific Advisor, Consulting fee. Neumedicine: Scientific Advisor, Consulting fee. Roche: Scientific Advisor, Consulting fee. T2 Biosystems: Scientific Advisor, Consulting fee. V. G. Fowler Jr., Merck, Cerexa/Actavis, Pfizer, Advanced Liquid Logis, NIH, MedImmune, Basilea, Karius, Contrafect, Regneron, Genentech, Affinergy, Locus, Medical Surface, Inc., Achaogen, Astellas, Arsanis, Bayer, Cubist, Debiopharm, Durata, Grifols, Medicines Co, Novartis: Collaborator, Consultant and Scientific Advisor, Consulting fee, Research grant and Research support.